Task shifting for musculoskeletal disorders in Norwegian primary care: a qualitative interview study of general practitioners and specialist musculoskeletal physiotherapists - Kenneth Chance-Larsen; Michael Backhouse; Richard Collier; Tobba Sudmann (Scandinavian Journal of Primary Health Care)
Objective To explore the views of general practitioners and physiotherapists on the current model of care for patients with musculoskeletal disorders in Norwegian primary care, and if the English First Contact Practitioner model, where patients have access to multiple professional groups with musculoskeletal health expertise, could inform service development.Design, setting, and subjects We analysed interviews with five GPs and 11 physiotherapists and used Lipsky’s theories about street-level bureaucracy and Foucault’s theories of mechanisms of power and institutional structures to explore task shifting and cooperation between different professions.Results and interpretation The empirical material reflected a multi-faceted discourse about skill-mix in primary care, where financial factors, perceptions about competence, and task preferences moderated attitudes to task shifting. Competition and cooperation coexist between the professions, and the seemingly gradual blurring between historical hegemony and new models of care creates both alliances and rivalries. Examples of deviations from the Choosing Wisely principles and evidence-based practice indicate that both general practitioners and physiotherapists balance the roles of patient advocate, gatekeeper, and homo economicus, in a context where task shifting is challenged by established practice. It appears that the management of patients with musculoskeletal disorders is fragmented and to some extent reflects a supply-driven system.